PURPOSE AND DIRECTION OF FUTURE RESEARCH IN MANAGERIAL HONESTY - Dwi Rendra Adi Putrawijaya; Ni Wayan Sulastri; Basuki Basuki (Universitas Jember, 2017)
The ultimate objective of this study is to describe a big picture of managerial honesty research that had been done in last decade. Moreover, the result of this research is aiming to provide an opportunity to continue the research on this particular topic. This archival study was held based on 21 research subjecting in managerial honesty, particularly in budgeting.Research that can be developed in this sphere is related to economic and psychological factors that affect conflict within the organization. Specifically, this research plan seeks to outline the economic and psychological factors affecting the competition. Furthermore, the research plan seeks to distinguish models from the competition and analyze their impact on management tendencies in conducting honesty in addition to economic incentives to lie. The model is here: first, the model that involves economic pressures and the second is a model that raises competition among participants without changing the number of monetary incentives. Keywords: Managerial Honesty, Budgetary Slack, Honesty on Budgeting